A tributação dos softwares como serviços: aspectos do ICMS e do ISSQN - Toschi, Caio Calzado (2023)
It is notorious and old the discussions about the multiple interpretations possible regarding the legal treatment, for tax purposes, of software’s license of use. However, due to the evolution of technological ways of software distribution, the discussions are present and challenge the understandings built in the past, aiming to the correct tax treatment to be given to operations involving such goods. Because of the potential tax collection that grows exponentially, laws are set forth and the understandings of tax authorities try to legitimate ICMS and ISS taxation of standard software, no matter how the program was delivered. In the courts, the matter is still unsettling, since the downloaded software tax treatment was defined only very recently and the evolution of technology is turning given way of distribution obsolete, with the migration for the distribution of the software as a service. From this evolution outlook, this study aims to analyze, from the legal and technical perspective, the adequate tax treatment to be given to this software as a service distribution operation, to verify whether it is a ICMS or ISSQN tax triggering event and point solutions that allow the effective recognition of its proper legal treatment, to give legal certainty to operations involving these kinds of goods